2022
DOI: 10.1039/d1gc03955e
|View full text |Cite
|
Sign up to set email alerts
|

Coke and sintering resistant nickel atomically doped with ceria nanosheets for highly efficient solar driven hydrogen production from bioethanol

Abstract: Using bioethanol steam reforming (ESR) to produce green hydrogen is restricted by the low activity, coke, sintering of Ni based catalysts as well as the consumption of fossil energy, which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…Based on the three peaks of O 1s shown in Figure b, the peaks at 529.3 and 531.8 eV could be assigned to the adsorbed oxygen (O L ) and lattice oxygen (O a ), respectively, and the characteristic peak at 530.6 eV belongs to O Vs . After the NIRR, the O Vs concentration decreased from 8.11 to 2.01% (Table S2), which was consistent with the XPS results of Ce . This decrease may be due to the enhanced molecular adsorption capacity of the active sites of FLPs, and the O atoms of the adsorbed NO 3 – filled the surface O Vs .…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Based on the three peaks of O 1s shown in Figure b, the peaks at 529.3 and 531.8 eV could be assigned to the adsorbed oxygen (O L ) and lattice oxygen (O a ), respectively, and the characteristic peak at 530.6 eV belongs to O Vs . After the NIRR, the O Vs concentration decreased from 8.11 to 2.01% (Table S2), which was consistent with the XPS results of Ce . This decrease may be due to the enhanced molecular adsorption capacity of the active sites of FLPs, and the O atoms of the adsorbed NO 3 – filled the surface O Vs .…”
Section: Resultssupporting
confidence: 83%
“…After the NIRR, the O Vs concentration decreased from 8.11 to 2.01% (Table S2), which was consistent with the XPS results of Ce. 41 This decrease may be due to the enhanced molecular adsorption capacity of the active sites of FLPs, and the O atoms of the adsorbed NO 3 − filled the surface O Vs . 40 In Figure 2c, due to the doping of C, a strong peak appeared at 284.2 eV, while the peaks at 285.8 and 288.2 eV could be attributed to the combination of C and surface O to form C− O and C�O.…”
Section: Resultsmentioning
confidence: 99%
“…The advantage of photothermal catalysis over photocatalysis is its high solar utilization potential, as it can theoretically absorb 100% of sunlight. Achieving a high sunlight absorption performance is fundamental to photothermal catalysis. Among various catalysts, metal materials are ideal catalysts for photothermal CO 2 conversion with the merits of a high photothermal conversion effect, excellent catalytic activity, and selectivity. ,, However, the light absorption ability of bulk metals is intrinsically poor, because the bulk metals have abundant nearly free electrons, which make the surface plasma frequency of bulk metals higher than most photons’ vibration of the sunlight spectrum .…”
Section: Nanostructured Materials Strategies For Improving Sunlight A...mentioning
confidence: 99%
“…The coupling of the photothermal device based on Bi 2 Te 3 /Cu with CuZnAl nanosheets shows promising solar-heating methanol steam reforming (MSR) activity, far exceeding all solar-powered methanol-to-hydrogen systems reported . Given the low IR radiation of Cu, a photothermal device based on the selective light absorber of Ti 2 O 3 thin layer/Cu film can also be constructed . Based on the heterostructure concept, Lou et al reported a Fe 3 Si aerogel with full sunlight absorption and 0.04 W m –1 K –1 of thermal conductivity.…”
Section: Nanostructured Materials Strategies For Improving Sunlight A...mentioning
confidence: 99%
“…RWGS consumes a large amount of non-renewable energy. 11,12 Photothermal catalysis has the potential to solve the energy bottleneck of RWGS and the heterostructure photothermal catalysis developed by Li et al could achieve 317 °C under 1 sun light illumination (1 kW m −2 of energy density), 13,14 able to drive RWGS under outdoor solar irradiation.…”
Section: Introductionmentioning
confidence: 99%